Studio minerogenetico delle miniere aurifere della regione di marmato (colombia) (1962)
Various veins of aproximately East-West strike and mineralized with auriferous pyrite, sphalerite and galena are present in the region of Marmato (Dep. Caldas ) , These veins are situated in a microdioritic orck of subvolcanic type and their origin is in the same magma which caused the intrusion of the microdiorite.